The Effect of Ammonium Concentration Addition to Gracilaria sp. on The Absorption of Mercury - Yudi Nurul Ihsan; Luthfiyyah Azizah; Kalysta Fellatami; Tri Dewi Kusumaningrum Pribadi (Jurnal Kelautan, 2022)
The research was conducted from March to June 2015 in the laboratory of Marine Science of the faculty of FPIK UNPAD. The sampling of Gracilaria sp. was taken from a seaweed farming in Kalianda, Bandar Lampung Province. The aim of conducting this research is to investigate the effect of Ammonium addition to Gracilaria sp. on the absorption process of Mercury. The proportion amount of 10.5-gram Gracilaria sp.  used in this research is mixed with 3 litres seawater media. The research method was performed using Completely Randomised Design (CRD) with four treatments and three replications. Parameters for the measurements are water quality, reduction of mercury and ammonium concentration, bio concentration factor, and growth rate. The research was designed with an addition of 0.05 ppm Mercury in all treatments, where each treatment was given different concentrations of Ammonium as follows: treatment A: 0.5 ppm, treatment B: 1 ppm, and treatment C: 1.5 ppm, with no addition of Ammonium for Control Treatment. The result of this research showed that treatment C hit the highest absorption level in absorbing Ammonium and Mercury with their concentrations of 95.98% and 56.44% respectively in seawater media, while the concentration of Mercury in the Gracilaria sp. biomass was measured 0.47 ppm.Keywords: Absorption, Ammonium, Gracilaria sp., Phytoremediation, Mercury.